Economic downturns and nurse attachment to federal employment. (22nd May 2019) - Li, Danyao; Richards, Michael R.; Wing, Coady
Abstract: The impact of the financial crisis has been uneven—with differences across industries and occupations. Jobs linked to health care appear better insulated, with nurses specifically showing labor force gains during the recent recession. What is not known is how important public sector employment opportunities are for these national nursing trends. Observing the universe of nurses working for one of the largest (and publicly operated) health care employers, we show that worsening economic conditions lead to stronger job attachment. Relatedly, older nurses also seem more willing to delay retirement and instead transition to part‐time positions during a downturn.